The Comparison Between Food Habits and Physical Condition Among Physical Education and Other Undergraduate Students [Comparación en Hábitos Alimentarios y Condición Física Entre Estudiantes de Educación Física y Otras Carreras Universitarias] - Herrera-Valenzuela, T (Grupo Aula Medica S.L., 2015)
Introduction: college students show a great susceptibility to acquire inadequate habits during their university studies, which they could maintain along their life. Objective: compare the dietary habits and physical fitness among physical education students and other university careers at the same university and campus. Methods: the sample included 343 students, mainly men (70%), 212 students from the career of Physical Education (PE) and 131 students of other careers (OC) of the Universidad Autónoma de Chile, Temuco campus. A validated survey about eating habits and physical fitness tests were applied to each student. Results: in comparison with the students from other careers, the men of PE have a lower frequency of consumption of dairy, vegetables, alcohol (p < 0.05) and women of PE have higher frequency of consumption of homemade food, biscuits and sweet snacks (p < 0.05). Regarding the physical fitness, PE students obtained the best performance as was expected. Conclusion: no major differences were observed among the eating habits of students PE and OC from the same university, while physical fitness is consistent with the greater stimulus that the PE students receive in their academic training, which would serve as a excuse to consume more sugary drinks, junk food, cookies and sweet snacks. © 2015, Grupo Aula Medica S.A.. All rights reserved.